The nucleocapsid protein of Newcastle disease virus promotes solubility of the VP2 hypervariable region of infectious bursal disease virus in Escherichia coli - Saadun, Rafidah; Wen, Siang Tan; Omar, Abdul Rahman; Bejo, Mohd. Hair; Eshaghi, Majid; Yusoff, Khatijah (Universiti Putra Malaysia Press, 2008)
The hypervariable region (HVR) of VP2 protein of infectious bursal disease virus (IBDV) elicits neutralising antibodies, but it is highly hydrophobic and tends to form inclusion bodies when expressed in Escherichia coli. To improve its solubility, the VP2(HVR) was fused to the C-terminal end of Newcastle disease virus (NDV) nucleocapsid (NP) protein and expressed in E. coli TOP 10 cells under the control of trc promoter. However, the fusion protein, NP-VP2(HVR)-trc, aggregated into insoluble inclusion bodies in the host cells. Therefore the coding region of NP-VP2(HVR) was sub-cloned into expression vectors containing the T7 promoter. The solubility of the NP-VP2(HVR)-T7 fusion proteins improved dramatically in E. coli BL21 (DE3), BL21 (SI) and Origami B cells.